Behaviour of Si, Al, Fe and Mg during oxidative sulfuric acid leaching of low grade uranium ore: A kinetic approach. Issue 3 (June 2019) - Madakkaruppan, V.; Pius, Anitha; Sreenivas, T.; Sunilkumar, T.S.
Highlights: Leaching kinetics of Si, Al, Fe & Mg on low grade uranium ore was investigated. The leaching mechanism was found to be diffusion controlled and through the product layer. Apparent activation energy was 7.86 kJ/mol for Si, 7.68 kJ/mol for Al, 4.14 kJ/mol for Fe and 7.26 kJ/mol for Mg respectively. XRD and SEM-EDS studies show that the oxidative sulfuric acid leaching process leads to leaching of both uranium and chlorite/biotite minerals. Abstract: This paper deals with the behavior of reactive micaceous gangue minerals like chlorite and biotite during the oxidative sulfuric acid leaching of uranium ores taking case study of a typical low grade Indian uranium ore hosted by chlorite-biotite-muscovite-quartzo-feldspathic schist. The progress of the gangue minerals chemical reactivity was monitored kinetically by analyzing the concentration of Si, Al, Fe and Mg ions in the leach liquor and through SEM-EDS analysis of feed and leach residue. The kinetic plots were analysed using shrinking core model and the rate equations deduced for all the aforementioned four elements constituting the gangue indicated significant role played by concentration of sulfuric acid, redox potential, temperature of reaction and particle size in the diffusion controlled process, which is also substantiated from the thermodynamic parameters computed. The results indicated decreased particle size, increased sulfuric acid concentration, longer contact time, higher rate of agitation and increased redox potential results in higher concentration of Si, Al, Fe, Mg and U.